PERKEMBANGAN FUNGSI DARIPADA DALAM SURAT KABAR ABAD KE-19 HINGGA ABAD KE-21 - Hanum, Nisa (Universitas Pembangunan Nasional “Veteran” Jawa Timur, 2000)
This study discusses the development of the function of daripada in Malay-Indonesian newspapers from the 19th to 21st centuries. This study aims to trace and outline functions of daripada used in the newspapers. This diachronic research uses data corpus from the newspaper Bintang Timor (19th century) and Kompas (20th and 21st centuries). The newspapers are taken from the roll film archived in the National Library of the Republic of Indonesia and e-paper on the official website of Kompas.id. The process of analysis and calculation of the functions was completed using Ant. Conc. Furthermore, the results are displayed descriptively in tables and diagrams. Based on the results of this study, there are eight functions of daripada. These functions are daripada as comparative markers, source markers, topic markers, causative markers, inceptive-time markers, possessive markers, exceptive markers, and negative markers. In the 19th century, eight of these functions emerged in varying frequencies. In the 20th century, there were only four functions that arose and survived, those were daripada as comparative markers, possessive markers, source markers, and topic markers. In the 21st century, there is only one function that arises and survives, that is daripada as a comparative marker. In general, from the 19th to 21st centuries, daripada was experiencing a narrowing of the meaning and function.